GENDER ROLES IN OPTIMISATION OF HOUSE-YARD LAND TO IMPROVE HOUSEHOLD INCOME (Case Study of Kampung Kucai in Kranggan Hamlet, Pojok Village, Blitar Regency) - Lintar Brillian Pintakami (JARES (Journal of Academic Research and Sciences), 2017)
This research aims to describe women farmer ’s participation in the establishment of Kampung Kucai (Chives Hamlet) through Women Farmers Group, to identify existing gender roles, and to review to what extent do women contribute to household income by means of house-yard land optimisation for farming practice. Study area was determined purposively in Kampung Kucai, Kranggan Hamlet, Pojok Village, Blitar Regency. This research was conducted between March and April 2018. Snowball sampling was used as sampling method. There were 20 respondents interviewed, both husbands and wives actively involved in Women Farmers Group, and 5 key informants. Data were analysed using descriptive analysis with qualitative and quantitative approaches. It was found that women ’s participation in the Kampung Kucai ’s establishment made up from chives cultivation, promotional activities, and managing sustainably. Gender roles in the house-yard land chives farming management were identified according to role/activity, control, access, and benefit disparities between men and women. Men were found to have allocated more time on productive role compared to their women counterparts. Men allocated 10 hours per day or 66,7 % worth productive role where women allocated 5 hours per day or 33,3 %. Therefore, each contributions to household income per month were Rp. 460.230,- and Rp. 229.770,- respectively, whereas women allocated more reproductive role than their men counterparts at 50 % rate compared to 14,5 %. Keywords: Gender Roles, Women Farmer, Workloads, Income Contribution. Received: 26 February, 2017; Accepter: 15 March, 2017